2021
DOI: 10.1016/j.cegh.2021.100764
|View full text |Cite
|
Sign up to set email alerts
|

Overweight/obesity risks and prevalence of diabetes and hypertension in North Eastern India: An analysis using seemingly unrelated probit model

Abstract: It would be reasonable to hypothesize that common unobserved factors, such as psychological stress and anxiety, as well as genetic and environmental factors, simultaneously influence the tendency for overweight or obesity and the prevalence of chronic disease. The paper tries to examine the joint influence of an individual's and socio-economic characteristics in determining overweight or obesity and chronic disease. Methods: The sample comprised of 112,062 male and female participants age 15-49 years. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
(41 reference statements)
1
8
1
Order By: Relevance
“…Also, a spurt in the prevalence of hypertension has been observed among individuals who consumed more than average amount of fructose 65. Evidence from a cross-sectional study in NE India supports the positive correlation between overweight or obesity with diabetes and hypertension 66 27. The plausible explanation is that both sugar sweetened beverages and artificial sweetened beverages are associated with the development of metabolic derangements that in turn might lead to elevated BP 67.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, a spurt in the prevalence of hypertension has been observed among individuals who consumed more than average amount of fructose 65. Evidence from a cross-sectional study in NE India supports the positive correlation between overweight or obesity with diabetes and hypertension 66 27. The plausible explanation is that both sugar sweetened beverages and artificial sweetened beverages are associated with the development of metabolic derangements that in turn might lead to elevated BP 67.…”
Section: Discussionmentioning
confidence: 99%
“…25 26 Notably, previous studies have examined patients with diabetes or hypertension as a single homogeneous group without considering the possible heterogeneity existing within the population. 27 Most of the existing studies on health risk behaviours have emphasised only changing a single unhealthy behaviour. 26 28 However, interventions that simultaneously target these unhealthy behaviours are necessary from the policy perspective.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…First, the set of covariates used was that most often considered in NCD risk evaluations. However, some relevant factors, such as dietary habits, physical exercise, smoking status, biomarker data, and alcohol consumption [ 12 , 14 ], which may increase the risk of hypertension and diabetes, were not captured, due to the unavailability of data. Thus, to implement this methodology for future work, we advocate the inclusion of those relevant available variables.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, studies have revealed that socioeconomic factors (such as low levels of educational status and high household wealth index) and demographic factors (such as age and gender—specifically, male) increase the risk of hypertension and diabetes [ 12 , 13 ]. Similarly, lifestyle behaviors (such as smoking and alcohol consumption) and dietary habits also significantly influence the risk of hypertension and diabetes [ 12 , 14 , 15 ]. Other studies and systematic reviews between 1980 and 2018 have shown an overall estimate of 57% for the frequency of hypertension [ 16 ].…”
Section: Introductionmentioning
confidence: 99%